Evaluation of clopidogrel impact on canine platelet function using flow cytometry and thromboelastography platelet mapping - Yoon, Eunchae; Shin, Chaewon; Bae, Hyeona; Cho, Kyu-Woan; Jung, Dong-In; Park, Jinho; Lee, Dongbin; Yu, DoHyeon (Frontiers in Veterinary Science, 2025)
BackgroundClopidogrel is frequently used in veterinary medicine to therapeutically decrease platelet function, although some different dosages have been published. Therefore, we assessed the antiplatelet effects of the recommended dosage (1 mg/kg PO q24h) on canine platelet function.MethodsFive dogs were administered either clopidogrel or placebo, with a 14-day washout period. Platelet function was assessed using thromboelastography (TEG) and flow cytometry, complete blood count, and biochemical analyses were performed for clinicopathological evaluation. Blood samples were collected at baseline and 7 days after drug administration. TEG parameters including maximum amplitude and platelet mapping for adenosine diphosphate (ADP)-induced responses were used to monitor therapeutic efficacy. Flow cytometry was used to analyze CD62P expression and platelet activation stimulated by ADP and other agonists.ResultsTEG analysis demonstrated a significant reduction in ADP-induced clot strength following clopidogrel administration (p < 0.05), indicating effective platelet inhibition. Flow cytometry confirmed the marked inhibition of platelet activation, with significant decreases in the percentage of CD62P positive platelets and the mean fluorescence intensity under ADP and epinephrine stimulation (p < 0.05). Hematological and biochemical parameters remained stable across all groups, confirming the safety of clopidogrel administration. These findings highlight the efficacy and safety of clopidogrel as an antiplatelet agent in dogs.ConclusionThis study confirmed the efficacy of low-dose (1 mg/kg, p.o., q24h) clopidogrel in dogs without a loading dose. TEG and flow cytometry are effective tools for assessing clopidogrel responsiveness in dogs and may aid in optimizing antiplatelet therapy in clinical practice.